The Key Factors for the Fate and Transport of Petroleum Hydrocarbons in Soil With Related in/ex Situ Measurement Methods: An Overview - Wang, Liang; Cheng, Ying; Naidu, Ravi; Bowman, Mark (Frontiers in Environmental Science, 2021)
When an oil spill occurs on land, the PHs undergo physical, chemical, and biological processes that further change their composition, toxicity, and distribution (partitioning) within the environment. Less volatile components will diffuse through soil in the non-aqueous phase liquid (NAPL) and be trapped in pores by sorption at mineral and organic matter surfaces. Vaporization from the NAPL, or desorption of sorbed molecules to the vapour or aqueous phases may also play an essential role in PH diffusion in soils. The highly volatile fraction will volatilize into the gas phase of the porous medium, from where it may be lost to the atmosphere, sorbed onto soil solids, or dissolved into soil water or groundwater. The NAPLs with high viscosity are more resistant to soil diffusion. The physical and chemical properties of the solid phase of soils, including texture, water and organic matter content, control the degree of hydrocarbon entrapment and sorption. The smaller soil particles have low porosity and permeability, resulting in significant hydrocarbon adsorption and holding capacity. Changes in the soil water content will inversely change the soil adsorptive ability. This is due to the competitive sorption of water in both vapour and aqueous phases with PHs in small soil capillaries. Soils with more substantial organic matter content absorb more PHs. This study reviews the critical factors for the sequestration of PH in diverse soil media. Furthermore, both of the ex-situ and in-situ measurement methods of determining these factors are also reviewed for PH contaminated site characterisation. The ex-situ measurements are usually conventional laboratory-based, while the in-situ methods are often coupled with portable and handheld instruments. The recent development of handheld/portable Fourier transform infrared spectroscopy (FTIR) instrument provides tremendous opportunities for in-field FTIR application. This study also critically reviewed the non-destructive FTIR spectroscopy analysis coupling with handheld FTIR for in-field PH contaminated site characterisation.